2003
DOI: 10.1539/joh.45.278
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of a Sense of Coherence and Natural Killer Cell Activity which Occurred in Subjects who Improved their Exercise Habits through Health Education in the Workplace

Abstract: independently of other psychological factors. These results suggest that subjects with improvement in exercise enhance NKCA through increased SOC in never smokers. (J Occup Health 2003; 45: 278-285) Key words: Exercise, Health education, Natural killer cell activity, Sense of coherence, Stress, Work SOC, a candidate for a mediating stress factor, is studied in the framework of Antonovsky's salutogenesis paradigm, which emphasizes the origin of health [1][2][3][4] . Life events stressors, depression and anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
4
12
1
Order By: Relevance
“…Takayama et al [32] showed that SOC is positively related to psychological health, which suggests the buffering effect of SOC on the maintenance of normal psychological health in dealing with stressful life events. We have previously demonstrated that SOC may be an important psychological modifier for determining lifestyle, including exercise and dietary habits [33], smoking behavior [34], and reaction to job stress [35]. Taken together with such a close relationship between SOC and stress coping, our results imply that inappropriate stress coping leads to body weight gain and to poorer psychological well-being.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Takayama et al [32] showed that SOC is positively related to psychological health, which suggests the buffering effect of SOC on the maintenance of normal psychological health in dealing with stressful life events. We have previously demonstrated that SOC may be an important psychological modifier for determining lifestyle, including exercise and dietary habits [33], smoking behavior [34], and reaction to job stress [35]. Taken together with such a close relationship between SOC and stress coping, our results imply that inappropriate stress coping leads to body weight gain and to poorer psychological well-being.…”
Section: Discussionsupporting
confidence: 61%
“…Taken together with such a close relationship between SOC and stress coping, our results imply that inappropriate stress coping leads to body weight gain and to poorer psychological well-being. Although life stress event and job stress including SOC are important risk factors for poor psychological well-being [11,33,34,36], our finding that low SOC leads to subsequent body weight gain in older workers is very striking. The cohort study followed-up over 14 years by Chandola et al [8,37], who examined cumulative work stress, using the Job Strain Questionnaire on four occasions, as a predictor of obesity in a prospective 19-year study of 6,895 men and 3,413 women (aged 35-55 years) in the Whitehall II cohort in London, UK (baseline: 1985-1988), reported a dose-response relationship between work stress and risk of general obesity (BMI 30 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 71%
“…Takayama et al (35) showed that SOC is positively related to psychological health, suggesting the buffering effect of SOC on the maintenance of normal psychological health in dealing with stressful life events. We previously demonstrated that SOC is also closely associated with exercise frequency (4) and smoking habit (5). On the basis of our findings, a low SOC score seems to be related to poor psychological well-being in elderly workers directly, or via lifestyle problems such as the lack of exercise, obesity, and smoking associated with a low SOC score.…”
Section: Discussionsupporting
confidence: 59%
“…Individual differences in SOC are associated with healthy life choices independently of social class and education, and may aid the design of future health promotion interventions 27) . Attempt has been made to enhance SOC in the workplace 11) , despite the fact that SOC is generally regarded as a stable personal factor which develops during the childhood and adolescence, and gradually reaches stability in early adulthood 1,28) . However, as evidence has been given that SOC considerably changes over a 4-yr period among a representative sample of Canadian labor force 29) , SOC can be increased by an appropriate intervention to improve stress-coping ability in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…In Japanese, SOC is reported to buffer the effects of stressful life events on mental health status 7) . Also, SOC is found to be associated with physical health issues such as the risk of coronary heart disease 8) and Type 2 diabetes 9) , serum cholesterol levels 10) , natural killer cell activities 11) , and incidence of external cause injuries 12) .…”
Section: Introductionmentioning
confidence: 99%